THE CONCEPT OF “TEACHING TECHNOLOGY” IN FOREIGN-LANGUAGE EDUCATION (The Journal of Interdisciplinary Human Studies, 2026)
This article clarifies the concept of “teaching technology” as applied toforeign-language (English) education. It traces the emergence of educational technologyin the mid-twentieth century from behaviourist psychology, Bloom’s taxonomy ofobjectives, and the systems approach to instructional design, and distinguishes theterm’s two principal readings – the technical means of instruction and the systematic,reproducible design of the teaching process. Drawing on the Russian-language traditionof “pedagogical technology” (Bespalko, Selevko) and on the methodological frameworkof applied linguistics (Anthony’s approach–method–technique), it relates the category of“method” to that of “teaching technology,” surveys the principal families of instructionaldesign (communicative, task-based, project-based, cooperative, game- and computerassisted), and sets out the criteria for selecting a technology in the conditions ofUzbekistan, including alignment with the Common European Framework of Referencefor Languages and with learners’ age. The article concludes by defining the technology ofteaching English as a scientifically grounded, procedurally organised, and reproduciblesystem for designing, conducting, and evaluating the teaching process
Keywords: teaching technology, educational technology, pedagogical technology, foreign-language teaching, method, English language teaching, instructional design, Common European Framework of Reference, communicative approach, task-based learning.